MANAJEMEN PERUBAHAN DALAM MENINGKATKAN KINERJA KOPERASI DI KABUPATEN PURBALINGGA - Bagus Gumelar; Candra Vionela Merdiana (Universitas Ahmad Dahlan, 2022)
This study examines the effect of change management in improving the organizational performance of cooperatives in Purbalingga Regency. Prior studies showed that cooperatives that excel in the long term are cooperatives that emphasize the ability to adapt to existing changes (resilience). However, during the Covid-19 Pandemic, cooperatives are now experiencing many obstacles that make cooperatives slower to develop and even decline the organizational performance. This study aims to explain the concept of organizational change and its benefits for the organization, providing essential ways to implement practices that improve the organizational performance of cooperatives in the Pubalingga Regency. The research sample in this study was 50 cooperatives in Purbalingga Regency as the respondents to the survey questionnaire. The analytical method used is multiple linear analysis. This study concludes that technological change has a positive and significant effect on organizational performance, organizational leadership change does not have a significant effect on organizational performance, and organizational cultural change has a significant effect on organizational performance.